Pilahing Watu - Ni Komang Vivi Larasati; Gusti Ayu Ketut Suandewi; I Putu Bagus Bang Sada Graha Saputra (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2025)
Pilahing Watu The Pilahing Watu Dance Work takes its creative source from a story in Beraban Village. About a village woman who was born or emerged from a split stone in Banjar Batu Gang or Batugaing. The story is raised with the theme of women, implementing female characters who have gentle, graceful, tough and majestic traits. The arranger collaborates with partners, namely the Pancer Langiit Art Studio in the process of realizing the Pilahing Watu Dance Work, starting from selecting movements to selecting music. The process of forming the Pilahing Watu Dance work uses an approach from I Kt. Suteja, namely Angripta sesolahan or creating dances. The Angripta sesolahan method consists of the stages of Ngarencana, Nuasen, Makalin, Nelesin, Ngebah and Presentation. The Pilahing Watu Dance Work uses six female dancers, using music from Swarapala which is also under the auspices of the Pancer Langiit Art Studio using the Gong Gede Saih Pitu Gamelan. It is hoped that this work can be enjoyed by many people, especially in Beraban Village, where the story originates. Keywords : Pilahing Watu, Split Stone, Beraban Village.